Performance of Employees at Wirosari District Office, Grobogan Regency Reviewed From Human Resources Development, Professionalism, Motivation, and Work Discipline - Niken Ning Tyas S; Kartika Hendra Titisari; Ida Aryati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The intention of this study is about to determine the simultaneous and partial influence between the variables of human resource development, professionalism, motivation, and work discipline on the performance of employees in the Wirosari District Office. This research method uses an associative research design. The population is all employees working at the Wirosari District Office, totaling 42 people. The sampling technique used in this study is a saturated sampling technique with a sample size of 42 respondents. Data collection using a questionnaire. This study uses the classical assumption analysis method, multiple linear regression test, model feasibility test (F test), hypothesis test (t test), and coefficient of determination using SPSS 25. The results of the study indicate that there is a significant influence between the variables of human resource development, professionalism, motivation, and work discipline both simultaneously and partially on employee performance. The influence of human resource development, professionalism, motivation, and work discipline simultaneously on employee performance in the Wirosari District Office is 88.3%, while 11.7% is influenced by other variables that are not examined. Keywords: Human Resource Development, Professionalism, Motivation, Work Discipline, and Employee Performance